Penerapan System Cloning Data Menggunakan AOMEI Partitions Assistant dan EaseUs ToDo Backup Terhadap Hardisk - Faizal Rapsan Yani; Galih Linggar Putra Pratama; Dora Parasuta; Tri Aldi Frandana (LPPM STIKI MALANG, 2022)
AOMEI Partition Assistant and Easeus Todo Backup are program applications that perform backup, recovery processes and are most often used for cloning a computer when performing maintenance that requires re-installation, providing benefits to simplify the process of cloning a hard drive. This research was conducted using a qualitative and experimental approach. This study was conducted in a computer laboratory at the Faculty of Information Technology, Merdeka University, Malang. In the laboratory there are 30 computers, but researchers only use 1 PC with 1 master hard drive on the main PC and 1 slave hard drive as the destination for data cloning results. Using the Easeus Todo Backup and AOMEI Partition Assistant cloning applications can make it easier to repair the Information Technology Faculty Laboratory, compared to Easeus Todo Backup, the AOMEI Partition Assistant application can already partition hard drives, both master and slave hard drives, and can process hard drive cloning to hard drive, hard drive to SSD or reverse. The application of the AOMEI Partition Assistant cloning application can also speed up the maintenance if a PC is damaged or laboratory construction requires a large number of operating system installations and requires a quicktime, the AOMEI Partition Assistant cloning application is very suitable to be implemented.